OPTIMASI TURN ARROUND TIME PADA PENJADWALAN ROUND ROBIN DENGAN MENCARI QUANTUM TIME OPTIMAL MENGGUNAKAN ALGORITMA SIMULATED ANNEALING - Asaziduhu Gea (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2015)
A number of processes that are queuing need has managed by the operating system so that all processes can be served without any process that is in decline or too long. The duration of the response time results in a number of subsequent process failed because it ran Burst Time which has been allocated to each process. One of the responsibilities of the operating system is managing the process by making scheduling and expected arround Turn Time is in getting smaller each time to execute a number of processes. Therefore, it is necessary to do the optimization of Turn arround Time. Round Robin algorithm uses fair scheduling method by evenly dividing the execution time (quantum time) for each process but continue to serve all these processes sequentially. Allocation quantum appropriate time greatly affect the average waiting time for the entire process of the Round Robin. Because it is necessary to do an effort to get a proper quantum time can give a little time to execute a number of processes by implementing Simulated Annealing algorithms. Simulated Annealing is a heuristic algorithm that is oriented to find a settlement solution of a problem with the minimal use of energy (time), but the results are quite large (number of processes that a lot). Tests carried out on the process by varying amounts. Every process has a different burst time and tested with the alpha value varies. Tests in each group showed that there was a decrease in the average waiting time is quite significant in the early iteration until the final iteration thus obtained Turn arround Time fewer, but the number of processes are executed more.